Declining Transmission and Immunity to Malaria and Emerging Artemisinin Resistance in Thailand: A Longitudinal Study. (3rd August 2017) - Ataíde, Ricardo; Powell, Rosanna; Moore, Kerryn; McLean, Alistair; Phyo, Aung Pyae; Nair, Shalini; White, Marina; Anderson, Tim J; Beeson, James G; Simpson, Julie A; Nosten, Francois; Fowkes, Freya J I
Summary: A 10-year-long evaluation of immunity to Plasmodium falciparum and emergence of artemisinin resistance showed that immunity declined sharply in the years preceding the emergence of parasites with artemisinin-resistant phenotypes and genotypes and was associated with faster parasite clearance times. Abstract: Background: Reductions in malaria transmission decrease naturally acquired immunity, which may influence the emergence of Plasmodium falciparum artemisinin-resistant phenotypes and genotypes over time. Methods: Antibodies specific for P. falciparum antigens were determined in uncomplicated hyperparasitemic malaria patients over a 10-year period of declining malaria transmission and emerging artemisinin resistance in northwestern Thailand. We investigated the association between antibody levels and both parasite clearance time (PCt½ ) and artemisinin resistance–associated kelch13 genotypes over time. Results: Immunity to P. falciparum declined prior to 2004, preceding the emergence of artemisinin resistance-associated genotypes and phenotypes (maximum mean change in antibody level per year: anti-MSP142 = −0.17; 95% confidence interval [CI] = −.31 to −.04; P = .01). In this period of declining immunity, and in the absence of kelch13 mutations, PCt½ increased. Between 2007 and 2011, levels of antibodies fluctuated, and higher antibody levels were associated with faster PCt½ (maximum yearly change in PCt½, in hours: EBA140rII = −0.39; 95% CI = −.61 to −.17; P < .001). Conclusions: Understanding the impact of changing transmission and immunity on the emergence of artemisinin resistance is important particularly as increased malaria control and elimination activities may enhance immunological conditions for the expansion of artemisinin-resistant P. falciparum .